The Correlation Between Speaking and Writing Ability of Non-English Education Department - Lia Kamilatun Nikmah; Agnes Melani; Retno Ayuning Tyas; Diah Kurniati (Prominent, 2024)
This research investigates the correlation between the speaking and writing abilities of first-semester students in the Management Study Program at Universitas Muria Kudus. Drawing on the perspectives of language learning theories and previous studies, the research aims to contribute to a better understanding of the relationship between these two productive language skills. The study employs a correlational design, utilizing scores from the Speaking and Writing courses as quantitative measures. The data analysis, conducted through statistical methods such as Pearson's correlation coefficient, explores the strength and direction of the relationship between speaking and writing abilities. The research is grounded in the belief that an integrated approach to language teaching is essential, and understanding the correlation between these skills can enhance language learning methodologies. The findings of this study have implications for language educators, curriculum developers, and researchers interested in the intersection of speaking and writing abilities among university students in non-English education programs.